Characterization of vaginal lactobacilli from HIV‐negative and HIV‐positive Indian women and their association with genital HIV‐1 shedding. Issue 10 (October 2017) - Mane, Arati; Angadi, Mansa; Vidhate, Pallavi; Bembalkar, Shilpa; Khan, Ishrat; Bichare, Shubhangi; Ghate, Manisha; Thakar, Madhuri
Abstract : Abstract : One of the crucial determinants for successful administration of lactobacilli to the vaginal niche is the use of appropriate Lactobacillus species. In this cross‐sectional study 54 human immunodeficiency virus (HIV)‐negative and 76 HIV‐positive antiretroviral treatment‐naïve women were evaluated for culturable vaginal lactobacilli and their association with genital HIV‐1 shedding. Lactobacillus species were identified by 16S rDNA sequencing while cervical and plasma HIV‐1 viral load was determined by Abbott real‐time PCR. Lactobacilli were isolated in 77.8% HIV‐negative and 73.7% HIV‐positive women. The mean log10 plasma and cervical HIV‐1 viral loads (RNA copies ml ‐1 ) were 3.73±1.02 and 2.85±0.32 respectively. We observed that presence of L. crispatus, L. gasseri or L. jensenii species was associated with undetectable cervical HIV‐1 ( P =0.046) and reduced genital HIV‐1 shedding ( P =0.048) compared to other species. Our findings endorse using Lactobacillus ‐based strategies to aid the prevention of HIV‐1 transmission among Indian women, however confirmation by future prospective studies is indeed warranted.